Metode Modifikasi Membran Polietersulfon (PES) Untuk Meningkatkan Antifoulingâˆ’Mini Review Modifikasi Membran - Enny Nurmalasari; Hasnah Ulia; Apsari Puspita Aini; Agung Kurnia Yahya; Yunita Fahni (Eksergi, 2023)
Polyethersulfone (PES) is the most common material in various medical and water treatment applications because of its excellent mechanical and thermal properties. The hydrophobicity of polyethersulfone is considered as one of the main drawbacks because the hydrophobic surface causes a high biofouling effect on the membrane, so it has limitations in using Polietersulfon PES membrane technology. Modification of PES membranes is an important topic to be continuously developed to improve the properties of PES membranes. Membrane modifications focus on increasing the hydrophilicity, selectivity, and stability of membranes that are expected to be used commercially. Modifications were made to change the hydrophobic membrane surface into a hydrophilic membrane with good mechanical properties by introducing hydrophilic properties and functional groups to the polyethersulfone membrane surface. This review includes reviews and discussions on modifying PES membranes by mixing, coating, and grafting methods. In particular, adding functional groups to polyethersulfone is a suitable method for introducing hydrophilic properties. The addition of nanomaterials to the surface of the polyethersulfone membrane by mixing, coating, grafting, and combinations significantly increases the surface of the membrane, and all modifications affect the surface roughness of the membrane.